2002
DOI: 10.1271/bbb.66.576
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Malate Synthase from the Glucose-grown Wood-rotting BasidiomyceteFomitopsis palustris

Abstract: Malate synthase (EC 4.1.3.2), the key enzyme of the glyoxylate cycle, was puriˆed to a homogeneous protein from the wood-rotting basidiomycete Fomitopsis palustris grown on glucose. The puriˆed enzyme, with a molecular mass of 520 kDa, was found to consist of eight 65-kDa subunits, and to have K m of 45 and 2.2 mM for glyoxylate and acetyl-CoA, respectively. The enzyme activity was competitively inhibited by oxalate (K i , 8.5 mM) and glycolate (K i , 17 mM), and uncompetitively by coenzyme A (K i , 100 mM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Moreover, we have suggested that F. palustris transports oxalate out of the cells to prevent possible inhibition of intracellular metabolic reactions. For example, oxalate might inhibit the activities of FPICL1 and malate synthase in peroxisomes of F. palustris (15,35), because oxalate competitively inhibits the activities of the two enzymes in vitro (30,31). In addition, oxalate produced from oxaloacetate by cytosolic OAAH in F. palustris (1,35) possibly shows product inhibition for OAAH activity because oxalate is a competitive inhibitor (K i ϭ 19 M) for OAAH from Botrytis cinerea (13).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have suggested that F. palustris transports oxalate out of the cells to prevent possible inhibition of intracellular metabolic reactions. For example, oxalate might inhibit the activities of FPICL1 and malate synthase in peroxisomes of F. palustris (15,35), because oxalate competitively inhibits the activities of the two enzymes in vitro (30,31). In addition, oxalate produced from oxaloacetate by cytosolic OAAH in F. palustris (1,35) possibly shows product inhibition for OAAH activity because oxalate is a competitive inhibitor (K i ϭ 19 M) for OAAH from Botrytis cinerea (13).…”
Section: Discussionmentioning
confidence: 99%
“…80 % by HPLC), the MIC value was 0.270 µM. We evaluated the effects of alkaloids 1 and 2 on PbMLS using pyruvic acid as a positive control [18][19]. Alkaloid 1 exhibited no inhibitory activity against PbMLS, but alkaloid 2 inhibited PbMLS with an IC 50 of 50 µM (l " Fig.…”
mentioning
confidence: 99%
“…10) Moreover, we have reported that the metabolic change occurs at the transient step from the vegetative growth to the fruit body formation of this basidiomycete; ICL, a key enzyme of the GLOX cycle, is more important in oxalate synthesis at the vegetative growth stage, and NADP-IDH is important for glutamate synthesis at the fruiting stage. 11) Furthermore, we have recently puriˆed and characterized the malate synthase (MS) 12) and ICL 13) involved in the GLOX cycle of the same fungus.…”
mentioning
confidence: 99%